HEATR3 recognizes membrane rupture and facilitates xenophagy in response to Salmonella invasion - Masashi Arakawa; Keiya Uriu; Koki Saito; Mai Hirose; Kaoru Katoh; Krisana Asano; Akio Nakane; Tatsuya Saitoh; Tamotsu Yoshimori; Eiji Morita (Proceedings of the National Academy of Sciences, 2025)
Bacterial invasion into the cytoplasm of epithelial cells triggers the activation of the cellular autophagic machinery as a defense mechanism, a process known as xenophagy. In this study, we identified HEATR3, an LC3-interacting region (LIR)-containing protein, as a factor involved in this defense mechanism using quantitative mass spectrometry analysis. HEATR3 localizes intracellularly invading Salmonella , and HEATR3 deficiency promotes Salmonella proliferation in the cytoplasm. HEATR3 also localizes to lysosomes damaged by chemical treatment, suggesting that Salmonella recognition is facilitated by damage to the host cell membrane. HEATR3 deficiency impairs LC3 recruitment to damaged membranes and blocks the delivery of the target to the lysosome. These phenotypes were rescued by exogenous expression of wild-type HEATR3 but not by the LIR mutant, indicating the crucial role of the HEATR3–LC3 interaction in the receptor for selective autophagy. HEATR3 is delivered to lysosomes in an autophagy-dependent manner. Although HEATR3 recruitment to the damaged membrane was unaffected by ATG5 or FIP200 deficiency, it was markedly impaired by treatment with a calcium chelator, suggesting involvement upstream of the autophagic pathway. These findings suggest that HEATR3 serves as a receptor for selective autophagy and is able to identify damaged membranes, facilitate the removal of damaged lysosomes, and target invading bacteria within cells.